The Relationship Between Exclusive Breastfeeding And Diarrhea In Children Aged 6-24 Months At Aek Parombunan Public Health Center, South Sibolga 2019 - Tamara Lubis; Dwi Rita Anggraini (Sumatera Medical Journal, 2021)
Diarrhea is a symptom of infection in the intestinal tract with the second death rate in the world in children under five years of age. Risk factors for the incidence of diarrhea in children under five are host factors that increase susceptibility to diarrhea, not giving exclusive breastfeeding (ASI), not giving breastfeeding for 2 years, malnutrition, measles and immunodeficiency. Breastfeeding (ASI) contains the best nutrients that match the needs of the baby and exclusive breastfeeding is carried out from birth to the first six months without any additional food or drink. Several studies have shown that the immunity content of breastfeeding is able to coat the gastrointestinal mucosa and protect the digestive tract from incoming pathogens. The aim of this study is to find out the relationship between exclusive breastfeeding and the incidence of diarrhea in children aged 6-24 months at Puskesmas Aek Parombunan, Sibolga Selatan in 2019. The research design used was observational analytic cross-sectional with the criteria for the research sample of toddlers aged 6-24 months. The sampling technique in this study used total sampling. The research instrument was a medical record and data analysis used the chi-square test. Based on the results of the study, there was a relation between exclusive breastfeeding and the incidence of diarrhea.